Anti-CD52 antibody treatment depletes B cell aggregates in the central nervous system in a mouse model of multiple sclerosis - Simon, Micha; Ipek, Rojda; Homola, Gyoergy A.; Rovituso, Damiano M.; Schampel, Andrea; Kleinschnitz, Christoph; Kürten, Stefanie (Journal of Neuroinflammation, 2018)
BACKGROUND: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) for which several new treatment options were recently introduced. Among them is the monoclonal anti-CD52 antibody alemtuzumab that depletes mainly B cells and T cells in the immune periphery. Considering the ongoing controversy about the involvement of B cells and in particular the formation of B cell aggregates in the brains of progressive MS patients, an in-depth understanding of the effects of anti-CD52 antibody treatment on the B cell compartment in the CNS itself is desirable. METHODS: We used myelin basic protein (MBP)-proteolipid protein (PLP)-induced experimental autoimmune encephalomyelitis (EAE) in C57BL/6 (B6) mice as B cell-dependent model of MS. Mice were treated intraperitoneally either at the peak of EAE or at 60 days after onset with 200 μg murine anti-CD52 vs. IgG2a isotype control antibody for five consecutive days. Disease was subsequently monitored for 10 days. The antigen-specific B cell/antibody response was measured by ELISPOT and ELISA. Effects on CNS infiltration and B cell aggregation were determined by immunohistochemistry. Neurodegeneration was evaluated by Luxol Fast Blue, SMI-32, and Olig2/APC staining as well as by electron microscopy and phosphorylated heavy neurofilament serum ELISA. RESULTS: Treatment with anti-CD52 antibody attenuated EAE only when administered at the peak of disease. While there was no effect on the production of MP4-specific IgG, the treatment almost completely depleted CNS infiltrates and B cell aggregates even when given as late as 60 days after onset. On the ultrastructural level, we observed significantly less axonal damage in the spinal cord and cerebellum in chronic EAE after anti-CD52 treatment. CONCLUSION: Anti-CD52 treatment abrogated B cell infiltration and disrupted existing B cell aggregates in the CNS.
EVALuna2:35209